2017
DOI: 10.17507/jltr.0801.02
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Language Teaching Strategies for German as a Foreign Language in Uganda

Abstract: Abstract-The communicative language teaching (CLT) approach emphasizes the change in the role of the teacher from a transmitter of knowledge to a facilitator of language learning. Teachers must therefore, develop and utilize teaching strategies that enable learners to freely interact in a classroom environment to enhance the required communicative competences. However, in the Ugandan context where the curriculum is examination-driven, teacher competence is judged on the basis of students' excellence in the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The CLT approach emphasises a change in the role of the teacher from being a transmitter of knowledge to a facilitator of language learning. Teachers must, therefore, develop and utilise teaching strategies that enable learners to interact freely in a classroom environment, with the purpose being to enhance the required communicative competences (Sekiziyivu and Mugimu, 2017). As observed by Snow (1996), learners effectively learn a language when they take part actively in its communication, rather than just passively accepting what the teacher says.…”
Section: Definition Of Communicative Language Teachingmentioning
confidence: 99%
“…The CLT approach emphasises a change in the role of the teacher from being a transmitter of knowledge to a facilitator of language learning. Teachers must, therefore, develop and utilise teaching strategies that enable learners to interact freely in a classroom environment, with the purpose being to enhance the required communicative competences (Sekiziyivu and Mugimu, 2017). As observed by Snow (1996), learners effectively learn a language when they take part actively in its communication, rather than just passively accepting what the teacher says.…”
Section: Definition Of Communicative Language Teachingmentioning
confidence: 99%
“…Therefore, students could benefit from CLT due to the assistance they gained from the effectiveness of the communicative strategies. Besides, it is suggested that teachers must be flexible while performing CLT in their classrooms, playing the role of facilitators of the teaching and learning process (Sekiziyivu & Mugimu, 2017).…”
Section: The Use Of the Communicative Language Teaching In The Classroommentioning
confidence: 99%
“…Communicative language teaching can also be viewed as a learner-centred approach to language teaching (Ying, 2010). CLT stresses the development of communication, and learners interact among themselves while the teacher acts as guide to helps learners acquire language in the teachinglearning process (Brown, 2001;Richards & Rodgers, 2001;Sekiziyivu & Mugimu, 2017). In principle, CLT is an approach that encourages interaction and allows learners to use language meaningfully and in context.…”
Section: Communicative Language Teaching In Zimbabwementioning
confidence: 99%